Current Strategies for Microbubble-Based Thrombus Targeting: Activation-Specific Epitopes and Small Molecular Ligands - Wang, Zhaojian; Huang, Huaigu; Chen, Yuexin; Zheng, Yuehong (Frontiers in Bioengineering and Biotechnology, 2021)
Microbubbles with enhanced ultrasound represent a potentially potent evolution to free drug administration in the treatment of thrombotic diseases. Conformational and expressional changes of several thrombotic biological components during active coagulation provide epitopes that allow site-specific delivery of microbubble-based agents to the thrombus for the theranostic purpose. Through the interaction with these epitopes, emerging high-affinity small molecular ligands are allowed to selectively target the thrombi with tremendous advantages over traditional antibody-based strategy. In this mini-review, we summarize recent novel strategies for microbubble-based thrombus targeting through epitopes located at activated platelets and fibrin. We also discuss the challenges of current targeting modalities and supramolecular carrier systems for their translational use in thrombotic pathologies.